Kesenjangan antara Harapan dan Kenyataan: Fenomena Kekecewaan Karyawan terhadap Organisasi - Djoko Wijono; Arundati Shinta (Jurnal Maksipreneur, 2012)
A tendency to compare between our output and other’s output, unfortunately, is evident on nearly every employee. A source of this tendency is the psychological contract between employee and organization. Based on that psychological contract, employees often felt that they were treated unfairly by organization compared to other employees. This kind of comparison phenomenon – known as wang sinawang (Javanese) – sadly is because the employee’s inability to compare objectively. This essay is addressed to discuss the psychological contract and strategy to make comparison more objectively through the equity theory. It is because almost all of employees – including ourselves – tend to compare to each other in daily activities.